2005
DOI: 10.1080/08111470500354265
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks in Public and Community Housing: The Impact on Employment Outcomes

Abstract: Abstract:This article seeks to examine some of the ways in which social networks may contribute to employment outcomes for community and public housing tenants. There is a body of literature that explores the relationship between social networks and employment outcomes, and a separate literature on the relationship between housing and social networks (which is largely concerned with homeowners). However, there has been little research that links all three aspects, especially in relation to social housing. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Saegert and Winkel (1998) argue that low-income housing cooperatives can constitute a type of 'ownership' and that even though the individual does not own the property: 'the opportunity to control living conditions appears to provide an incentive similar to homeownership, even though financial incentives of homeownership is missing ' (p. 50). A recent Australian study also found that the range of activities involved in living in cooperatives, in terms of tenant control and responsibility for managing the housing, makes it more similar to homeownership than other rental tenures (Ziersch & Arthurson, 2005;Arthurson, Ziersch & Long, 2006). In addition, Saegert and Winkel (1998) argue that relationships and norms of trust and reciprocity that develop through these management experiences are the key to making this form of cooperative ownership successful.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Saegert and Winkel (1998) argue that low-income housing cooperatives can constitute a type of 'ownership' and that even though the individual does not own the property: 'the opportunity to control living conditions appears to provide an incentive similar to homeownership, even though financial incentives of homeownership is missing ' (p. 50). A recent Australian study also found that the range of activities involved in living in cooperatives, in terms of tenant control and responsibility for managing the housing, makes it more similar to homeownership than other rental tenures (Ziersch & Arthurson, 2005;Arthurson, Ziersch & Long, 2006). In addition, Saegert and Winkel (1998) argue that relationships and norms of trust and reciprocity that develop through these management experiences are the key to making this form of cooperative ownership successful.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study comparing Housing Authority housing, tenant owned cooperatives, community groups and private landlords, Saegert and Winkel (1998) found that residents of tenant owned cooperatives had higher levels of involvement in both tenant associations and informal social interaction with other residents. Likewise, in a comparison of public and community housing tenancies, Ziersch and Arthurson (2005) found that community housing tenants tended to have stronger ties with their neighbours than public housing tenants. In part, this finding appears to reflect the need for cooperative tenants to collaborate with neighbours in order to undertake the necessary tasks of running the cooperative.…”
Section: Housing Tenure and Social Capitalmentioning
confidence: 99%
See 3 more Smart Citations